PENGARUH PENGAWASAN INTERNAL, AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN SLEMAN (SURVEI PADA SELURUH SATUAN KERJA PERANGKAT DAERAH KABUPATEN SLEMAN) - Bambang Jatmiko (Jurnal Akuntansi Trisakti, 2020)
This study aims to discuss and prove Internal Oversight, Accountability and Transparency of Local Government Performance. This research was conducted in all Regional Work Units in Sleman Regency which obtained 48 SKPD. The research method usessurvey, quantitative data and types of data consisting of primary data obtained by distributing questionnaires that will be distributed to all SKPDs with 144 respondents and 122 questionnaires that can be reprocessed. The sample in this study were government employees who met the specified criteria.. The results of the study indicate that (1) Internal Supervision shows positive and significant impact on the performance of the Regional Government of Sleman Regency. (2) Accountability influences positively and significantly on the performance of the Regional Government of Sleman Regency. (3) Transparency affects positively and significantly on the performance of the Regional Government of Sleman Regency.